Characterization of in Vitro ADME Properties of Diosgenin and Dioscin from Dioscorea villosa - Manda, Vamshi K.; Avula, Bharathi; Ali, Zulfiqar; Wong, Yan-Hong; Smillie, Troy J.; Khan, Ikhlas A.; Khan, Shabana I. (Planta Medica, 2013)
Dioscorea villosa (wild yam) is native to North America and has been widely used as a natural alternative for estrogen replacement therapy to improve womenʼs health as well as to treat inflammation, muscle spasm, and asthma. Diosgenin and dioscin (glycoside form of diosgenin) are reported to be the pharmacologically active compounds. Despite the reports of significant pharmacological properties of dioscin and diosgenin in conditions related to inflammation, cancer, diabetes, and gastrointestinal ailments, no reports are available on ADME properties of these compounds. This study was carried out to determine ADME properties of diosgenin and dioscin and their effects on major drug metabolizing enzymes (CYP 3A4, 2D6, 2C9, and 1A2). The stability was determined in simulated gastric and intestinal fluids (SGF, pH 1.2 and SIF, pH 6.8), and intestinal transport was evaluated in Caco-2 model. Phase I and phase II metabolic stability was determined in human liver microsomes and S9 fractions, respectively. Quantitative analysis of dioscin and diosgenin was performed by UPLC-MS system. Dioscin degraded up to 28.3 % in SGF and 12.4 % in SIF, which could be accounted for by its conversion to diosgenin (24.2 %. in SGF and 2.4 % in SIF). The depletion of diosgenin in SGF and SIF was < 10 %. Diosgenin was stable in HLM but disappeared in S9 fraction with a half-life of 11.3 min. In contrast, dioscin was stable in both HLM and S9 fractions. Dioscin showed higher permeability across Caco-2 monolayer with no significant efflux, while diosgenin was subjected to efflux mediated by P-glycoprotein. Diosgenin and dioscin inhibited CYP3A4 with IC50 values of 17 and 33 µM, respectively, while other CYP enzymes were not affected. In conclusion, dioscin showed better intestinal permeability. Conversion of dioscin to diosgenin was observed in both gastric and intestinal fluids. No phase I metabolism was detected for both compounds. The disappearance of diosgenin in S9 fraction indicated phase II metabolism.
Keywords: Dioscorea villosa; Dioscoreaceae; diosgenin; dioscin; Caco-2; metabolic stability; CYP inhibition; intestinal transport